El gobierno de la archidiócesis de Zaragoza en el pontificado de Juan Soldevila (1902-1923) / The government of the archdiocese of Saragossa in the pontificate of Juan Soldevila (1902-1923) - Santiago Casas Rabasa (Studia et Documenta)
The government of the archdiocese of Saragossa in the pontificate of Juan Soldevila (1902-1923) Josemaría Escrivá was formed as a priest mainly in the archdiocese of Saragossa. There he studied as a seminarian, received the diaconate, the priesthood and took on his first pastoral assignments. The priestly condition seemed essential to him in order to be more open and available to whatever God might ask of him in the future. Perhaps not from a theoretical point of view, but from a practical one, in Saragossa he had his first knowledge of how a diocese was administered and how the power of government was exercised within the Church. This power was exercised in Saragossa by Cardinal Soldevila and his auxiliary bishop Díaz Gómara. Although the exercise of the episcopal function underwent a theoretical and practical change after the Second Vatican Council, the period of St Josemaría’s formation as a priest was marked by the example of these two prelates and their ‘cursus honorum’ gives an idea of what was expected of a prelate both from the point of view of the Holy See and of the diocesan faithful.